The prognostic value of the preoperative albumin-to-fibrinogen ratio in patients with intrahepatic cholangiocarcinoma: a multicenter retrospective propensity score matching analysis - Yang, Yakai; Kong, Junjie; Wang, Tao; Ji, Min; Li, Guangbing; Liu, Jun (Frontiers in Oncology, 2025)
BackgroundThis study evaluated the prognostic role of the albumin-to-fibrinogen ratio (AFR) in patients with intrahepatic cholangiocarcinoma (ICC) after curative liver resection.MethodsRetrospectively analyzed the clinicopathological information of ICC patients and stratified them into two groups by AFR (8.71). A 1:3 propensity score matching (PSM) analysis was used to eliminate possible biases. Kaplan-Meier method was used for survival analysis. Independent prognostic factors for overall survival (OS) and disease-free survival (DFS) were analyzed using Cox regression analysis, and based on which two nomograms were constructed. The concordance index (C-index), decision curve analysis (DCA), calibration curve, and receiver operating characteristic (ROC) curve were used to validate the nomograms.Results559 patients were included and were divided into low- and high-AFR groups, respectively. High-AFR group had better prognosis. The multivariate analysis revealed that AFR was an independent prognostic factor for both OS (hazard ratio [HR] 0.393, P < 0.001) and DFS (HR 0.538, P < 0.001). Two nomograms were established to predict OS and DFS, and demonstrated high predictive accuracy and clinical utility. Furthermore, ROC curves demonstrated the high predictive power of the nomogram for survival in ICC patients.ConclusionsPreoperative AFR was an independent prognostic factor for postoperative OS and DFS in ICC patients, and AFR-based nomograms effectively predict postoperative survival outcomes.